Entrepreneurship Principles and Ecological Awareness: A Qualitative Analysis in the Context of the Bakti Enzyme Community - Ambarita, Prini Desima Evawani; Darmawan, Cecep; Rahmat, R.; Syaifullah, S. (Jurnal Manajemen Bisnis, 2024)
This study explores the relationship between entrepreneurship and ecological awareness with a focus on the Enzim Bakti community, using a descriptive qualitative approach. The Enzim Bakti community, known for its efforts in utilizing enzymes to support environmentally friendly practices, serves as a case study to understand how entrepreneurship can be integrated with the principles of ecological sustainability. Through in-depth interviews, observations, and document analysis, this study identifies various aspects of entrepreneurship implemented in this community and their impact on the ecological awareness of its members. The results show that entrepreneurship in the Enzim Bakti community is not only focused on creating economic value but also contributes significantly to environmental sustainability goals. Community members develop innovations that are oriented towards waste reduction, resource efficiency, and maintaining environmental quality. Ecological awareness, instilled through education and daily practices, plays a significant role in shaping entrepreneurial strategies that support environmental goals. These findings highlight that the integration of sustainability principles in entrepreneurship can have positive impacts on both business and the environment, and provide insights into how entrepreneurial communities can contribute to broader ecological awareness.